Information technology and social movements: a study in the Free Pass movement - Moraes, Gustavo Hermínio Salati Marcondes de (2017)
In recent years, Brazil has witnessed protests organized by a group called Free Pass Movement. In 2013, the main demand was against the raise of the price for public transportation, and complaints were expanded to the political system, health and education demands, corruption and spending on the 2014 World Cup. In 2015, public protests returned to the national political scene. The use of social networks as people’s communication vehicle to show dissatisfaction was widely used as well as a means of articulation of groups. This study aimed to identify the factors that led people to use social networks to participate in the protests, with 257 respondents who took part of the Free Pass Movement. Results show the factors that positively influence the use of social networks with protest purposes and demonstrate the respondents’ disbelief regarding some positive effect to solve public management problems.